Cyclic testing reliability analysis on a novel light-curable bone fixation technique - Cameron, Paula M. N.; Hutchinson, Daniel J.; Malkoch, Micheal; Varga, Peter; Schwarzenberg, Peter (Frontiers in Bioengineering and Biotechnology, 2025)
Metal fixation is currently the standard of care for treating bone fractures surgically, as it provides ample stability to the healing bone. However, metal components have been associated with soft tissue adhesions and are generally not patient specific. A novel light-curable bone fixation method, called AdhFix, overcomes these disadvantages by allowing for in situ customizability and demonstrating a lack of soft tissue adhesions. Previous studies on this fixation technique have demonstrated the maximum bending and torsional moments in monotonic failure tests in dry conditions. However, this fixation has yet to be tested cyclically in a more physiological environment, which would represent an important step to assessing the clinical efficacy of this technology. This study aims to test the novel fixation method cyclically at relevant force levels in a controlled near-physiological environment. Midshaft osteotomies were performed on ovine proximal phalanges which were then fixated with the AdhFix osteosynthesis technique. The constructs were tested cyclically in four-point bending for 12,600 cycles, representing 6 weeks of rehabilitation, or until failure, while submerged in Ringer solution at 37°C. The samples were divided into four groups, each tested with a different peak force. The peak forces were based on safety factors (Group 1: 100x, Group 2: 150x, Group 3: 175x, Group 4: 250x) of a physiological bending moment present in a human proximal phalanx osteosynthesis during rehabilitation exercises, determined in a previous study. All samples survived at the lowest peak moment (Group 1), whereas all failed at the highest peak force (Group 4). Kaplan-Meier curves represented the survival probability as a function of the number of cycles for each group, and a log-rank test revealed that the survival curves were significantly different (p < 0.001). The difference in patch height between the failures and survivors was not statistically significant (p = 0.113), but the final cycle displacement amplitude was statistically different (p < 0.001). This study found that this novel osteosynthesis method can survive a clinically relevant number of cycles at a force level 100× the bending loads involved in typical non-weight-bearing rehabilitation exercises. Further studies are needed to confirm safety for other conditions.